The roles of influencers endorsement of local skincare brands on online purchase intention - Yura Nada Khairunnisa; Rifelly Dewi Astuti (President University, 2022)
Regardless significant roles of influencers in brand communication strategies, there are still some issues about the factors that may determine the strength of their influence and how the power of influencers can influence their followers in shaping perception and behavior towards the brands they support. This study aims to determine the role of the perceived information value and emotional attachment in the influencer's influence process, which later creates the expected value of the brand, brand engagement in self-concept, and the intention to buy the recommended brand. This research will be conducted with quantitative research. The context of this research is Indonesian local skincare products which contribute to local manufacturers in developing communication strategies for their products. The results of 300 respondents as a sample show that perceived information value and emotional attachment are determinants of the perceived influence, and the power of influence of influencers increases brand engagement and brand value will have an impact on the intention to purchase the recommended product. Besides, brand engagement also increases brand value, and brand value also affects purchase intention. The findings of this study contribute to a better understanding of the effect of an influencer's persuasion. The implications for practitioners and researchers are also discussed in the study.